2020
DOI: 10.1016/j.healun.2019.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-flow ex vivo lung perfusion to rehabilitate lungs donated after circulatory death

Abstract: BACKGROUND: Current ex vivo lung perfusion (EVLP) protocols aim to achieve perfusion flows of 40% of cardiac output or more. We hypothesized that a lower target flow rate during EVLP would improve graft function and decrease inflammation of donation after circulatory death (DCD) lungs. METHODS: A porcine DCD and EVLP model was utilized. Two groups (n = 4 per group) of DCD lungs were randomized to target EVLP flows of 40% (high-flow) or 20% (low-flow) predicted cardiac output based on 100 ml/min/kg. At the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Using the EVLP platform of isolated lung perfusion, our group previously demonstrated that lower lung perfusion flows provide better rehabilitation. 26 This likely occurred through reduction of shear stress on the vasculature, which aided in maintaining the integrity of the endothelium and limited hydrostatic edema. Therefore, our IVLP protocol targeted a low left lung perfusion goal of 8% of cardiac output, which may also play a role in reduction of pulmonary edema.…”
Section: Discussionmentioning
confidence: 99%
“…Using the EVLP platform of isolated lung perfusion, our group previously demonstrated that lower lung perfusion flows provide better rehabilitation. 26 This likely occurred through reduction of shear stress on the vasculature, which aided in maintaining the integrity of the endothelium and limited hydrostatic edema. Therefore, our IVLP protocol targeted a low left lung perfusion goal of 8% of cardiac output, which may also play a role in reduction of pulmonary edema.…”
Section: Discussionmentioning
confidence: 99%
“…We however, used 20% of calculated CO, as we believe that this amount of perfusion provides the lung with ample perfusion and decreases shear stress on the endothelium. 9 Additionally, we calculated the tidal volume using 6 ml per kilogram butchered bodyweight, which does not include the weight of the skin and head of the sheep. Important to note is that we did not add perfusate nor remove metabolites, to see the unadulterated effect of EVLP on sheep lungs and the perfusate.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol we presented here is similar to the original porcine EVLP protocol as established by Steen et al 8 Using 40% of the calculated living cardiac output as max flow rate, is seen in many EVLP setups. We however, used 20% of calculated CO, as we believe that this amount of perfusion provides the lung with ample perfusion and decreases shear stress on the endothelium 9 . Additionally, we calculated the tidal volume using 6 ml per kilogram butchered bodyweight, which does not include the weight of the skin and head of the sheep.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ali et al 121 recently demonstrated that with repeated EVLP and cold ischemic preservation, they could extend total preservation time to 3 d. Other experiments have demonstrated that EVLP time can be extended by modifying aspects of EVLP protocols such as ventilator settings, perfusate composition, perfusion flow, temperature, and supplemented nutrients. [122][123][124][125][126][127][128] If this concept of extended EVLP for prolonged graft preservation can be successfully demonstrated in clinical EVLP, it would be absolutely advantageous for broader graft sharing. Additionally, acutely damaged lungs, for example, from an active infection, aspiration, or traumatic injury, raise substantial concerns for favorable transplant outcomes and cannot be used for transplant currently.…”
Section: The Next Generation: Approaches Under Investigationmentioning
confidence: 99%